Psychography of Terrorist Religiosity: A Case Study in East Java - Takdir, Mohammad; Basri, Basri; Sidik, Mohamad Dindin Hamam (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2023)
Based on the psychographic theory of Glock and Stark, this study tries to provide more information about the terrorist's religiosity in the context of a suicide bombing in East Java, Indonesia. To understand the theological state of terrorists who commit suicide bombings in the name of jihad, this research takes a psychological approach. Through later suicide bombings, which frequently occur, this research uses qualitative techniques to paint a picture of the dimensions of religiosity that terrorists possess. The Surabaya suicide bombings in East Java are used as a case study in this paper. The researcher uses psychographic theories of religion, which encompass ideological, ritualistic, intellectualistic, experiential, and consequential elements, to evaluate the religious dimensions of terrorists. This study demonstrates that a terrorist's religiosity can be characterised as having only conceptual, ceremonial, and intellectualistic aspects; the experiential and consequential aspects are not evident in the terrorist's attitude or personality.